Thermal stability of bio-based calcium and aluminum carboxylates (International Journal of Biology and Chemistry, 2026)
As bio-based metal carboxylates, calcium and aluminum carboxylates were synthesized using sunflower oil and soybean wax as renewable feedstocks, and their structures were characterized by Fourier-transform infrared spectroscopy (FT-IR). The FT-IR results confirmed the successful formation of the corresponding metal carboxylates. Thermogravimetric (TG) and differential thermal analysis (DTA) techniques were employed to evaluate the thermal stability of the synthesized compounds. According to the thermal analysis data, aluminum carboxylates exhibited faster thermal decomposition compared to calcium carboxylates, with the major decomposition step occurring predominantly in a single stage. The higher thermal stability of calcium carboxylates relative to aluminum carboxylates can be attributed to their low-er organic content and, additionally, to the fact that calcium forms more stable compounds due to its higher chemical reactivity, a trend that was clearly reflected in the TGA curves. Consequently, calcium carboxylates underwent multi-stage decomposition. This behavior was also evident in the DTA profiles, where the heat absorption and release events showed a fluctuating pattern. Given the significant industrial relevance of metal carboxylates as additives in polymer and lubricant formulations, understanding their physicochemical properties is essential.Keywords: metal carboxylates, metal soaps, calcium carboxylates, aluminum carboxylates, thermal stability, addi-tives, bio-based additives, sunflower oil